Microbiological and Ecophysiological Characterization of Green Algae Dunaliella sp. for Improvement of Carotenoid Production - ainuri, Muhammad Z; Kusumaningrum, Hermin P.; Kusdiyantini, Endang (Jurnal Natur Indonesia, 2008)
An isolate of green algae Dunaliella sp. from BBAP Jepara is usually used as a source for carotenoid supplementfor marine animal cultivation in the local area. In order to improve carotenoid production especially detection ofbiosynthetic pathway from the organisms investigated in this study, the main purpose of this study is characterizingDunaliella sp. based on it’s microbiological and ecophysiological characters. The research was done by characterizethe growth, the cell and colonies microbiologically, total pigment production, and also characterize all of theecophysiological factors affecting the algal growth and survival. The results of this research showed that Dunaliellasp. posseses typical characteristic of green eucaryote alga, in their growth and ecological condition. The extremecharacters which was toleration ability to high salinity environment of was used to conclude Dunaliella sp. asDunaliella salina.